National Culture and Perceived Ethics of Tax Evasion: Case of Bali Province - I Nyoman Kusuma Adnyana Mahaputra; Ni Wayan Rustiarini; Ni Putu Nita Anggraini; I Made Sudiartana (Journal of Economics, Business, and Accountancy Ventura, 2018)
This study aims to investigate the relationship of national cculture and taxpayer's ethical perception of tax evasion. National culture dimensions include powner dinstance, uncertainty avoidance, individualism/ccollectivism, masculinity/femininity, lOng/shurt tarm orientation, and indulgence/rrestraint. This study employes survey method, using online questionnaires for taxpayers who haveself employment in Bali Province.Three hundred and seventy seven taxpayers fillend out online questionnaires. This model is processed using multiple linear regression analysis method. The results indicate that power distance, uncertainty avoidance, individualism/collectivism, and femininity/masculinity are associated with perceived ethics of tax evasion, but do not associated between short term/long term orientation and indulgence/restrain with perceived ethics of tax evasion. This study is expected to improve knowledge about tax evasion especially related to national culture. Practically, the results are expected to provide input for tax regulators to consider the role of national culture in identifying the causes of tax evasion.